Annual Report of AsiaBlight-China in 2021 and Workplan for 2022 - Xingbi, C. (2021)
The AsiaBlight Network operates and works replying on CCCAP’s arrangement. which is an open and inclusive non-profit cooperation and exchange platform composed of scientists, entrepreneurs, growers, agricultural technology extension workers and administrative decision-makers committed to solving the problem of late blight in the Asia Pacific region. Its purpose is to serve potato farmers - 1 -in the Asia Pacific region and improve the ability to solve potato late blight in the region. At present, the AsiaBlight Network has more than 300 members in China. The existing professional monitoring and prediction points of potato late blight have reached more than 900 stations (these 900 monitoring points can also be regarded as sales outlets of fungicide enterprises), increasing more than 200 units over the previous year. AsiaBlight Network coordinators are distributed in the main potato-producing areas in China and provide technical support and professional services to prevent and control late blight for local farmers.